Hodgkin–Huxley Artificial Synaptic Membrane Based on Protonic/Electronic Hybrid Neuromorphic Transistors. Issue 2 (15th January 2018) - Fu, Yang Ming; Wan, Chang Jin; Zhu, Li Qiang; Xiao, Hui; Chen, Xiao Dong; Wan, Qing
Abstract: Iontronics is a newly emerging interdisciplinary concept that bridges electronics and ionics. It provides new opportunities for biomimic information processing. Iontronic devices can act as building blocks for neuromorphic platforms. Here, a proof‐of‐principle Hodgkin–Huxley artificial synaptic membrane is proposed for the first time based on inorganic proton conductor. Phosphosilicate glass‐based proton conductor electrolyte demonstrates unique short‐term volatile charging behaviors, indicating potential short‐term synaptic plasticity applications. By using protonic/electronic hybrid oxide transistor configuration, dynamic synaptic membrane potential responses are triggered with gate current spikes. Typical resting potential, excitatory/inhibitory postsynaptic potential behaviors, and membrane depolarization/activation behaviors are mimicked on the proposed Hodgkin–Huxley artificial synaptic membrane. Moreover, proton‐related electrostatic coupling enables the device to possess short‐term synaptic plasticities with low power consumption. The proposed Hodgkin–Huxley artificial synaptic membrane provides a new prototype for neuromorphic system applications. Abstract : A Hodgkin–Huxley artificial synaptic membrane is proposed based on protonic/electronic hybrid oxide neuromorphic transistor. Typical resting potential, excitatory/inhibitory postsynaptic potential and membrane depolarization/activation behaviors are mimicked. Proton‐related electrostatic coupling enables the neuromorphic transistor to possess short‐term synaptic plasticities with low power consumption. The results provide a new prototype for neuromorphic cognitive system applications.